আত্নচরিত : সংযোজন, ইংলন্ডের ডায়েরী, Men I have seen - শাস্ত্রী, শিবনাথ, ১৮৪৭-১৯১৯. (কলকাতা : দে'জ পাবলিশিং, 2003)
Autobiography of a 19th century Bengali author and Brahma-samaj member from Bengal, India.
"Prasaṅga, Śibanātha Śāstrī, Rabīndranātha Ṭhākura, Rāmānanda Caṭṭopādhyaẏa, Girijāśaṅkara Rāẏacaudhurī, Bipinacandra Pāla, Premāṅkura Ātarthī."
Originally published: Kalikātā : Prabāsī Kāryālaẏa, 1918.
Donated By Akbar Ali Khan
In Bengali; one article in English.
Keywords: Śāstrī, Śibanātha, -- 1847-1919.; Authors, Bengali -- 19th century -- Biography; Brahma-samaj members -- India -- Bengal -- Biography